Effect of mannan-rich fractions and a mixture of sodium butyrate and zinc proteinate on performance, intestinal morphometry, and gene expression in broilers - M. A. S. Silva; V. Ribeiro Júnior; C. M. Silva; L. F. C. Silva; A. P. Del Vesco; G. M. Oliveira Junior; A. A. Calderano; F. C. Tavernari; A. Corassa; C. O. Brito (Italian Journal of Animal Science)
This study evaluated the effects of isolated or combined prebiotics blended with sodium butyrate and zinc proteinate on performance, intestinal morphometry, and expression of genes associated with nutrient transport and immune response in broilers. 1,400 birds were randomly assigned to 5 treatments (Negative control (NC) without antibiotic; Positive control (PC) with antibiotic; Prebiotic (Prebio) composed of mannan fractions; Blend, composed of sodium butyrate, hydrolysed yeast cell wall and zinc proteinate; and the combination Prebio + Blend), with eight replications and 35 birds per experimental unit. The PC led to higher weight gain (WG) and lowered feed conversion (FCR) from 1 to 7 days of life than the other treatments. The use of prebio and blend resulted in high WG from 22 to 42 days (1773; 1768.9 g, respectively). However, the combination of prebio + blend was similar to PC and NC treatments. The additives resulted in longer duodenal villi when administered alone and in ileal villi (p = 0.001) combined, with no effect on jejunal villi. Crypt depth and duodenal villus: crypt ratio was higher for both additives types. A significant difference among treatments in the expression of the sodium-dependent glucose transporter gene (SGLT1) was noted, with greater expression in birds that received NC. There was higher expression of the neutral and cationic amino acid transporter gene (y + LAT-2) with the prebio and blend, either alone or in combination. The prebio blend with sodium butyrate and zinc proteinate additives used separately in broiler diets supported beneficial changes in intestinal morphometry, nutrient absorption, and performance, indicating their value in antibiotic-free broiler production systems.